Pengaruh Varian Produk Indomie Terhadap Keputusan Pembelian Konsumen Studi Kasus Di Kecamatan Tengah Tani Kabupaten Cirebon - Dewi Laily Purnamasari; Dewi Maharani Purbasari; Adinda Nur Kholifah (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of product variant variables and consumer purchasing decisions which are expected to increase the percentage of sales on Indomie products. The population used in this study was the school-age population in Tengah Tani Subdistrict, Cirebon Regency, amounting to 15,814 people. This research method uses area sampling technique. To determine which population will be used as a data source, the sampling is based on a population of 15,814 people, taking the sample using amounted to 105 school-age residents in Tengah Tani District, Cirebon Regency. Data were obtained from questionnaires which were then analyzed using the SPSS program. The results showed the results of the regression equation as follows: Y = 10.100 + 0.675 X. Hypothesis testing using the t-test showed that the two independent variables with a t-value of 8.227 and a t-table of 1.660 that were studied were proven to have a significant effect on the dependent variable. Figures R of 0.630 and R Square of 0.397 indicate that 39.7% of product variance can be explained by independent variables in the regression equation. So from these results, the factors that become the basis for consumers to buy Indomie products are so many product variants, and the many product variants in each type of product. Therefore, the quality of these factors must be maintained and it would be better if the quality should be further improved. With better quality, it is not impossible that Indomie products will become one of the products that are in great demand by the public. Keywords: Product variant, Consumer Purchase Decision, Indomie Products